PENGARUH APLIKASI TRICHOKOMPOS DALAM MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN EDAMAME (Glycine max L. (Merrill)) - Diana Y. L. Serangmo; Agnes V. Simamora; Gabriela C.G. Pratama (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
To increase edamame production, one of the things to consider is the availability of nutrients, which can be provided through the addition of organic fertilizers, for example, trichocompost. Trichocompost plays a role in increasing crop production because it can increase soil fertility and contains the antagonistic fungus Trichoderma sp., capable of controlling plant pathogens. This study aimed to determine the growth response and yield of edamame due to the dose and time of application of trichocompost fertilizer. This research was carried out at the Undana Archipelago Dry Land Integrated Field Laboratory from October 2020 to June 2021. The study used a factorial randomized block design with two factors. The first factor was the dose of trichocompost (A), which consisted of four levels, namely A1=control, using the recommended NPK dose for edamame, which was 2.4 g/plant, A2=240 g of trichocompost/plant, A3=480 g of trichocompost/ plant, and A4=720 g of trichocompost/plant. The second factor was the application time of trichocompost (B) which consisted of three levels, namely B1 = application of trichocompost two weeks before planting, B2 = application of trichocompost one week before planting, and B3 = application of trichocompost at planting. Parameters observed were plant height, number of leaves, number of pods per plant, number of seeds, fresh plant weight, and seed dry weight. The results showed that the interaction between the doses of trichocompost fertilizer and the application time of trichocompost had no significant effect on all observational parameters. However, there was a tendency that trichocompost at a dose of 720 g/plant applied two weeks before planting had a higher number of pods, seeds, fresh weight, and dry weight of plants compared to the other treatments.